Sketsa Pendidikan Humanis Religius - Agus Sutiyono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The principle of education humanistic make from progressivism, namely child centered education. The teacher has a democratic and cooperative role, participation in student activity. Learning process and activity based student, it is a problem solving. Education is not only with target to humanistic but need transcendental target. Morality become is very important in this educational model, how created someone can meaningfulness it self and another. Education can build morality and capacity to realization living goal is it a style education humanism religious. Finally all person in this live can taste comfortable to ibtigha’a mardlatillah and radliyatan mardliyyah.